ANALISIS UNJUK KERJA PROTOTIPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO TURBIN PELTON SUMBER DAYA HEAD POTENSIAL - Syarif, Aida (KINETIKA, 2019)
The increase in population has an impact on increasing the demand for electricity in various sectors. Indonesia's geographical conditions with a tropical climate and high rainfall make Indonesia has many water sources that have the potential as a source of renewable electricity such as micro-hydro power. Research on Prototype of Microhydro Power Plant Pelton Turbine of Potential Head Resource laboratory scale by utilizing potential energy of water and using application on Pelton Turbine. There are two types of variables taken, including fixed and not fixed. Fixed variables in the form of flow direction, water volume and penstock cross-sectional area, while the not fixed variable in the form of difference in height and valve opening. Performance Analysis Prototype of Micro Hydro Power Plant uses the basic equations that is applied on the calculation analysis to determine the best performance analysis of the generating power of 9 watts is located at of head 1.8 m by opening full valve or flow rate variation of 140.5 Liter Per Minute with number of 16 blades. The results of optimum performance analysis of the plant are on different altitudes of PLTMH performance shows best performance in different of head 1.4 m by opening valve Â½ or 60.8 Liter Per Minute flow rate variation with the result of 20.71%